Zelens′kyi uses his communication skills as a weapon of war. Issue 2 (3rd July 2022) - Dyczok, Marta; Chung, Yerin
ABSTRACT: Ukraine's President Volodymyr Zelens′kyi's communication skills have proven to be a powerful weapon against Russia's disinformation war towards Ukraine. When Russia launched its full-scale military invasion of Ukraine in February 2022, he began recording daily messages to Ukrainian society and reaching out to international audiences through live addresses. This paper analyzes Zelens′kyi's speeches during the first 50 days of the intensified war. It examines the agenda-setting and framing methods, honed by his television experience, that he used to reach audiences, as well as their content. It suggests that these speeches made Ukraine's narrative dominant in international media, dispersing the information fog Russia was trying to create whereby Ukraine needed to be "de-Nazified, " neutralized, and kept in Russia's sphere of influence. They also helped consolidate Ukrainian society and strengthen international assistance.